Proposing a multilevel approach for the management of uncertainties in exploratory projects - Gomes, Leonardo Augusto de Vasconcelos et al (Project Management Journal)
Managers of exploratory projects might face uncertainties over long timeframes at different levels (e.g., project, portfolio, organization, and network). Although literature offers some guidance on how to deal with uncertainties (mainly at the project level), there is a need for more empirical ground and theoretical development of a systemic approach to the management of uncertainties. To fill this gap, this article employs a multiple case approach in two established firms, investigating six exploratory projects. As main contributions, we identified new categories of uncertainties (primitive, structural, and elementary) and aspects related to managing these uncertainties. - Reproduced.
Keywords: Innovation management; Exploratory projects